Exploring sports injury rates and demographics in several sports disciplines - Yaseen, Ali Mseer; Fathi, Rafia Salah; Mahmood, Haider Fawzi (Journal of Sports Research, 2025)
Knee injuries caused by sporting activities in various types of sports could be diverse mainly due to differences in the physical nature of the sport, participants’ profiles, and the intensity of training involved. This research sought to explore patterns in the prevalence of five common knee injuries: meniscal tears, acute anterior cruciate ligament (ACL) injuries, patellar instability, tendinopathy, and patellofemoral syndrome in three strike-related sports. A cross-sectional study involving 275 athletes participating in sports such as athletics, basketball, boxing, karate, soccer, jiu-jitsu, judo, kickboxing, kung fu, Greco-Roman wrestling, and volleyball was conducted. Data were obtained from medical histories and standardized self-administered questionnaires, with injury prevalences classified accordingly. Injury patterns and demographic variables, including age and sex, were statistically analyzed using descriptive statistics. The most common locations of ACL injury were found to be in football and judo, while laceration/testing mobility of the patellar tendons and patellofemoral syndrome were more prevalent in kickboxing and Greco-Roman wrestling. The study also revealed age differences across sports, with the youngest injured athletes participating in Greco-Roman wrestling. The results of this study are valuable for establishing sport-specific patterns of knee injury and highlight the necessity of targeted prevention and recovery strategies. Successful interventional programs should consider both individual and demographic attributes of athletes and the biomechanical demands of their respective sports.